THE ROLE OF BRAND IMAGE MEDIATES THE INFLUENCE OF SOCIAL MEDIA MARKETING AND CONTENT MARKETING ON PURCHASE DECISIONS: A STUDY ON CONSUMERS OF UMAH LOKAL COFFEE & ROASTERY IN DENPASAR - Pratama I P.A.; Yasa N.N.K. (Eurasia: Economics & Business, 2023)
As a result of the country's rapid modernization and rising middle class, the coffee industry in Indonesia is ripe for the picking. Umah Lokal Coffee & Roastery is seeing the effects of the rising levels of rivalry in the coffee sector, where new coffee shops are opening every year and the products sold are mostly interchangeable. The purpose of this research is to clarify how brand image moderates the impact of social media marketing and content marketing on consumers' final purchasing decisions. Umah Lokal Coffee & Roastery customers in Denpasar City make up the studies demographic. Purposive sampling, which is not based on probability, was used to calculate the sample size, which came to be 180 people in total. The data collection is carried out with the use of a Google Form questionnaire, and it is disseminated via a variety of social media platforms in addition to in-person surveys carried out at each of the many study locations. In this particular piece of study, the data were examined by making use of the Structural Equation Modeling (SEM) methodology as well as the Partial Least Square (PLS) strategy. Both of these methods were used in conjunction with one another. The following are some of the conclusions that can be drawn from the findings of this study: SMM and CM have a positive and significant effect on purchase decision; SMM and CM have a positive and significant effect on brand image; brand image has a positive and significant effect on purchase decision; and brand image can partially mediate the influence of SMM and CM on purchase decision. It is hoped that the findings of this study will contribute to the growing body of knowledge about marketing management and consumer behavior, as well as serve as a guide for management as they consider how to use social media and content marketing to strengthen the Umah Lokal Coffee & Roastery brand and encourage more people to buy their coffee.